Information system application for hotel department integration: A case study of Melia Purosani Hotel Yogyakarta - Rachmawati, Maria Anggraeni; Wardana, Wisnu Febri (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2022)
Tourism industry is a large field including hotel business. Hotel business is classified by its stars from non-star hotel to five-star hotel that has their own regulation to grow their own business. Hotel is divided by a lot of departments such as front office, food and beverage, housekeeping, accounting, sales and marketing, human resources, kitchen, and engineering. To integrate each department, the business needs information system to build connection one and another department. According to case study in Melia Purosani Hotel Yogyakarta, the business is using application and form business intelligence. Melia Purosani Hotel Yogyakarta is one of five-star international chain hotel in Yogyakarta that use system named Oracle Hospitality: Opera which is integrating one and another department. Opera creates convenience and ease the teamwork of each department, therefore the hotel could make guest satisfaction. Business performance management, data governance, business intelligence program, data architecture, data warehouse and lacking, also data integration is provided by Opera, therefore Melia Purosani Hotel Yogyakarta is belong to business intelligence. Business intelligence is required for big and professional business. Hence, a lot of data is protected and integrated one another.